Plasticity during Vestibular Compensation: The Role of Saccades - MacDougall, Hamish G.; Curthoys, Ian S. (Frontiers in Neurology, 2012)
This paper is focussed on one major aspect of compensation: the recent behavioural findings concerning oculomotor responses in human vestibular compensation and their possible implications for recovery after unilateral vestibular loss (UVL). New measurement techniques have provided new insights into how patients recover after UVL and have given clues for vestibular rehabilitation. Prior to this it has not been possible to quantify the level of function of all the peripheral vestibular sense organs. Now it is. By using vestibular-evoked myogenic potentials to measure utricular and saccular function and by new video head impulse testing to measure semicircular canal function to natural values of head accelerations. With these new video procedures it is now possible to measure both slow phase eye velocity and also saccades during natural head movements. The present evidence is that there is little or no recovery of slow phase eye velocity responses to natural head accelerations. It is doubtful as to whether the modest changes in slow phase eye velocity to small angular accelerations are functionally effective during compensation. On the other hand it is now clear that saccades can play a very important role in helping patients compensate and return to a normal lifestyle. Preliminary evidence suggests that different patterns of saccadic response may predict how well patients recover. It may be possible to train patients to produce more effective saccadic patterns in the first days after their unilateral loss. Some patients do learn new strategies, new behaviours, to conceal their inadequate VOR but when those strategies are prevented from operating by using passive, unpredictable, high acceleration natural head movements, as in the head impulse test, their vestibular loss can be demonstrated. It is those very strategies which the tests exclude, which may be the cause of their successful compensation.